PERAN ENTERPRISE RISK MANAGEMENT DALAM MEMEDIASI HUBUNGAN ANTARA TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Syihabudin Al Bustomi; Natatsa Rizqina Mubarika; Bramastyasa Gilang Pradata (Universitas Muhammadiyah Bengkulu, 2024)
This study aims to examine the effect of corporate governance on company value in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This study examines the influence of Enterprise Risk Management (ERM) as a mediating variable in the relationship between corporate governance and company value. The population in this study are manufacturing companies listed on the IDX in 2017-2019. The sampling method used was purposive which ultimately obtained 435 samples. The analytical tool used in this research is structural equation modeling (SEM) - Partial Least Square (PLS). The test results show that corporate governance which includes the number of boards of commissioner’s meetings has no effect on company value and the financial expertise of the risk management committee shows a positive influence on company value. Indirect testing revealed that ERM affects the relationship between the board of commissioners' meetings and the financial expertise of the board of commissioners on company value. ERM mediates corporate governance with corporate values. Keywords: Enterprise Risk Management, Risk Management Committee Financial Expertise